2022
DOI: 10.4103/jpbs.jpbs_92_22
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Based Analysis on Neck and Low Back Pain among Dental Practitioners- A Systematic Review

Abstract: This systematic review was undertaken to assess neck and back pain in dental practitioners. Published articles from 2015 onwards were explored in search engines of Pubmed, Medline, Scopus and Journal of web for outcomes of neck and back pain in dental practitioners. A total of 13 articles were reviewed, after carefully considering the eligibility criteria. The prevalence of neck and back pain was considerably higher, with neck pain occurrence ranging from 13.02% to 84.6% and back pain observed in 15.7% - 88.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Studies from top-ranked medical journals report that the low back and hip are areas highly affected by musculoskeletal disorders among dental professionals [ 3 , 4 , 5 , 7 , 10 , 11 , 12 ]. A high prevalence of low-back pain among dentists has been evidenced in several clinical studies [ 3 , 5 , 7 , 10 ], ranging from 48.5% [ 7 ] to 64% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies from top-ranked medical journals report that the low back and hip are areas highly affected by musculoskeletal disorders among dental professionals [ 3 , 4 , 5 , 7 , 10 , 11 , 12 ]. A high prevalence of low-back pain among dentists has been evidenced in several clinical studies [ 3 , 5 , 7 , 10 ], ranging from 48.5% [ 7 ] to 64% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…An Australian research group reports a low-back pain prevalence ranging from 36.3 to 60.1% (21 studies, dentists, n = 1428) [ 11 ]. A recent systematic review from a Saudi Arabia research group reported a prevalence of 15.7–88.9% (13 studies, n = 3443 dentists) [ 12 ]. Another recent systematic review and meta-analysis from an Indian research group reported a prevalence of 47.7% (6 studies, n = 2098 dentists) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The consequences of MSD for the employee and employer are significant, often resulting in reduced productivity, decreased job satisfaction, increased stress levels, higher rates of absenteeism and presenteeism, greater reliance on medication, a reduction in overall quality of life, and early retirement from the profession. 4,5,13,14 Models of MSD causation are numerous and encompass a complex inter-relationship of potential risk factors. Roquelaure et al 15 proposed a multidimensional model of work-related MSD health comprising individual (eg, lifestyle), physical (eg, biomechanical stressors), psychosocial (eg, work demands), and organizational workplace factors (eg, organization and management practices) that are subject to external influences from the economic, social, and political environment.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary search of PROSPERO, MEDLINE, the Cochrane Database of Systematic Reviews, and JBI Evidence Synthesis identified 9 review articles on MSD in oral health professionals published in 2022 and 2023, 9,10,12,13,16,20,[23][24][25] covering a mix of aims and objectives, and often including more than one domain of interest. Of these, 7 reviewed MSD prevalence rates, 2 investigated risk factors associated with MSD, and 3 evaluated MSD interventions.…”
Section: Introductionmentioning
confidence: 99%